Vaccine hesitancy in patients presenting to a specialized allergy center: clinical relevant sensitizations, impact on mental health and vaccination rates - Kogseder, Natalie; Puxkandl, Viktoria; Hoetzenecker, Wolfram; Altrichter, Sabine (Frontiers in Immunology, 2024)
Background: The COVID-vaccination program with new types of vaccinations and early reports of allergic reactions to vaccines led to vaccination hesitancy in patients with allergies. In this study, we aimed to characterize patients who present at an allergy center with specific questions regarding risk assessment to COVID vaccines in comparison to regular allergy center patients. Methods: 50 patient charts of patients with risk assessment for COVID vaccination (COV-group) and 50 regular allergy center patients (ALL-group) were assessed for documented allergies, comorbidities, total IgE and tryptase levels and hospital anxiety and depression score (HADS). Skin Prick-Testing (SPT) with additives of COVID-vaccines (polyethylenglycol (PEG), polysorbate) were performed if indicated based on medical history. Results: Patients who presented for examination prior to a possible COVID vaccination were mostly female (86%), had more frequently reported allergic reactions to drugs in the past, but only in a minor group (28%) reactions were qualifying as anaphylaxis. COV-group patients scored significantly higher in the HADS for anxiety and depression than regular ALL-group patients. The same trend was observed when data were corrected for gender. Of note, patient without any prior contact to COVID-vaccines scored comparable regarding anxiety to patients with prior reaction to COVID-vaccinations, but significantly higher in the depression score. In 19 patients (38%) who met the indications for SPT for the suspicious contents PEG and Polysorbate 80, tests did not show a positive result. 84% of patients who underwent Prick-Test but only 15% of patients who received consultation alone agreed to vaccination at our center. No vaccination related event was documented in these patients. Conclusion: In conclusion, vaccination hesitancy was frequently elicited by negative experiences with drugs and putative drug allergies. Females predominate in this patient group and anxiety and depression scores were significantly elevated. Allergological workup including SPT led to a high rate of subsequent vaccinations, whereas discussion with patients about risks and individualized advice for vaccination without testing only rarely resulted in documented vaccinations.